Bioactivity and anthocyanin content of microwave-assisted subcritical water extracts of Manipur black rice (Chakhao) bran and straw - Kamaljit Moirangthem; Priya Ramakrishna; Mahetab H. Amer; Gregory A. Tucker (2021)
Chakhao, the Geographical Indication (GI) tagged aromatic black rice of Manipur, India, is a rich source of bioactive compounds such as anthocyanins. However, there is limited work available on Chakhao and research has focused on its grain. No reports on the anthocyanin, antioxidant properties or in vitro bioactivities of its straw are available. Anthocyanins content of its different fractions displayed a positive correlation with their antioxidant potentials (r = 0.90). In this study, microwave-assisted sub-critical water extraction, at 90 °C for 5 min, from the straw gave an anthocyanins extraction efficiency of 85.8%. Furthermore, this microwave extract displayed higher antioxidant activity than an equivalent conventional methanol extract. In vitro studies on the microwave extracts of both straw and bran showed no apparent cytotoxicity on Jurkat cells and dose-dependent inhibition of colony growth in colorectal cancer cells. Black rice bran and straw are valuable by-products of the food industry that are rich in phytochemicals. This study reports the extraction of anthocyanins from black rice straw and presents evidence that the straw, in addition to the bran, contains important bioactive compounds; the extracts of which could further be explored as a natural antioxidant and/or functional ingredients.